Factors intended to brain drain among nurses working at private hospitals of Biratnagar, Nepal - Kadel, Mamata; Bhandari, Menuka (BIBECHANA, 2018)
Introduction: The migration of health worker is a complex and multifaceted phenomena. Emigration of highly skilled and competent nurses to other countries seems to have negative impact on the delivery of excellent health care services. Objective: The objective of this study was to assess factors intend to brain drain among nurses working at private hospitals of Biratnagar. Methodology: A cross sectional study was conducted on staff nurses of selected hospitals of Biratnagar, Nepal from 2017 February to 2018 February; non-probability purposive sampling technique was used. Required information was collected using self-administered semi structured questionnaire related to demographic and factors intending to brain drain from 99 nurses. Results: Majority (78.8%) of nurses were below 25 years of age. Most (81.8%) of them had completed PCL nursing, more than half (55.6%) wanted to migrate abroad to pursue further work and study. Australia (56.4%) and USA (25.5%) emerged as the top destination of choice, while only (5.5%) of them wanted to migrate United Kingdom. Lack of career opportunities, low salary and poor working condition were main pull factors and push factors intending to brain drain among nurses. This study also found that majority (96%) of nurses were not satisfied with their salary. Conclusion: More than half of nurses working in private hospitals would like to migrate abroad. The major push factors for migration was lack of career development and low salary. BIBECHANA 16 (2019) xx -xx